Ethnopharmacological Survey of Herbal Remedies Used for the Treatment of Cancer in the Greater Casablanca-Morocco - Bourhia, Mohammed (Evid Based Complement Alternat Med, 2019)
Medicinal plants played an important role in traditional medicine for the treatment of diseases since antiquities. The aim of the study is to carry out an ethnobotanical survey on medicinal plants used traditionally in cancer treatment in the region of Greater Casablanca-Morocco, and to enhance the traditional herbal medicine knowledge. 110 traditional healers in the study area were interviewed face to face to response a survey questionnaire including the names of plants used in cancer treatment, used parts, methods of preparation, and route of administration. Indices of Fidelity Level (FL), Use Value (UV), and Relative Frequency of Citation (RFC) were calculated to identify the most effective plants used for cancer treatment. Eight species were specified including Aristolochia baetica, Aristolochia paucinervis, Bryonia dioica, Aquilaria malaccensis, Marrubium vulgare, Lavandula maroccana, Ephedra alata, and Euphorbia resinifera belonging to 7 families. Aristolochiaceae, Aquilariaceae, and Cucurbitaceae were the most useful families in cancer treatment with high significant indices of UV, FL, and RFC with values of 1, 100%, and 1, respectively. Roots and leaves were the most commonly used plant parts. Decoction and powder mixed with honey were the frequently used method for remedies preparation. The present study showed that the people living in Morocco's economic capital are still highly dependent on traditional herbal medicine for the treatment of cancer. Therefore, it seems that herbal medicine still plays a crucial role in the primary healthcare system for the local population. During this survey, it was reported that even some plant families are highly toxic for humans like Aristolochiaceae that are frequently used in cancer treatment in the study area. As many people still rely on natural traditional medicine considering (it is safe with no side effects), so combined effort between all social categories including scientists and traditional healers should be established for involving the scientific validity of the used plants in the treatment of diseases.